The Role Of The economic And External Factors In Selecting Aggregate Planning Alternatives For Workforce Case Study In Yarmouk Teaching Hospital - داود غسان قاسم; خليل علياء محمد (Journal of Economics and Administrative Sciences, 2013)
The research aimed to achieve many objectives represented in two variables, which are the impacted factors and the aggregate planning alternatives of workforce in Educational Al- yarmouk Hospital , This research started from a problem focused on finding solutions to the demand’s fluctuation or the energy limitation while the study importance is emerged from diagnosis the suitable strategy and adopt the suitable alternatives due to their importance in meeting the demand for the health service submitted by the hospital .This study based on choosing assumptions of connection relationship and the impact among the mentioned variables in the(surgery and internal diseases) departments. The research is dependent on check least as tool of analysis application of research. The research reached conclusions such as limited attempts to manage the hospital in order to diagnose the factors affect on planning the work power of which has affected negatively on its ability in determining the suitable alternatives in order to face the clear shortage in the medical stuff to meet the increasing demand on the health service. The research has concluded to many instructions ,the most important one is to take care and develop the diagnosis of the factors affected on work power plans to reach strategy which achieves the hospital objectives represented in submitting the necessary health services of community.